IMPROVING STUDENTS’ ABILITY IN WRITING ENGLISH TEACHING BY USING PORTFOLIO ASSESSMENT : (An Experimental Study at SMKN 1 Blang Pidie) - Zuhri Efendi (Getsempena English Education Journal, 2017)
The objective of this study is to investigate whether the improving students’ ability in writing English teaching by using portfolio assessment. The method is used in this research is pre-experimental with one-group pre-test and post-test design. The population of this research was all grade X SMKN 1 Blangpidie. However, the sample of this research consisted of 30 students of the grade using purposive sampling technique. The instruments used in this study were test. The data of the research were collected through tests (Pre-Test and Post-Test). The pre-test was given before treatment and post-test was given after treatment. The data collected from pre and post-tests were analyzed by using t paired sample test through SPSS 16.00 shown that sig (0.000 < 0.05). The results found implementation portfolio assessment improve students’ writing skill. Therefore, the hypotheses of this study were accepted. There were significant improvement of students’ writing skill by using portfolio assessment. It can be concluded that the used of portfolio assessment increase students’ writing skill.